2018
DOI: 10.1007/s10072-018-3448-5
|View full text |Cite
|
Sign up to set email alerts
|

Circulating irisin and chemerin levels as predictors of seizure control in children with idiopathic epilepsy

Abstract: Irisin and chemerin peptides expression are triggered by hypoxia and involved in activation of inflammatory cascades in various organs including the brain; however, their role in epilepsy is not fully illustrated. This study aims to explore the predictive role of irisin and chemerin for seizure control in children with idiopathic epilepsy. This cross-sectional comparative study included 50 children with idiopathic epilepsy; 25 of them had controlled seizures over the previous 6 months and 30 age- and sex-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Irisin was also studied in Egyptian children with epilepsy. Children with idiopathic epilepsy presented higher irisin levels compared with controls [46]. Plasma irisin showed a positive correlation with the severity of seizures and the duration of the disease, probably playing a role as a predictor of uncontrolled seizures.…”
Section: Association Of Circulating Irisin and Other Diseasesmentioning
confidence: 99%
“…Irisin was also studied in Egyptian children with epilepsy. Children with idiopathic epilepsy presented higher irisin levels compared with controls [46]. Plasma irisin showed a positive correlation with the severity of seizures and the duration of the disease, probably playing a role as a predictor of uncontrolled seizures.…”
Section: Association Of Circulating Irisin and Other Diseasesmentioning
confidence: 99%
“…In summary, in previous studies, significant alterations were reported in ghrelin [15][16][17][18] , irisin 20 , FNDC5/irisin 18 , and nesfatin-1 16,18 levels. Despite this, there is also lack of evidence of whether these four neuropeptide levels are altered with drug resistant temporal lobe epilepsy (DRTLE) or not.…”
Section: Introductionmentioning
confidence: 62%
“…In a previous study, it was found that chronic antiepileptic drug treatment (valproate) decreased the PTZ-induced increase in serum and brain irisin levels in PTZ-kindling in rats 18 . Significantly increased serum levels of irisin were reported in children with idiopathic epilepsy 20 . These controversial results may have been associated with different factors; the present study conducted on adults and the subjects had therefore received longer antiepileptic drug therapy.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Meanwhile, it could be discovered in our results that SpO 2 nadir was related to AHI and irisin, which means that SpO 2 nadir may be regarded as intermediate pathway to connect AHI and irisin. It is reported that irisin expression is triggered by hypoxia-induced sympathetic activation and involved in activation of inflammatory cascades in various organs [ 40 42 ]. Also, some previous studies showed that irisin functioned as a protective factor by upregulating the cellular antioxidants, sustaining mitochondrial membrane potential, and reversing ATP production to counter the free radical damage induced by hypoxia [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%